PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN PADA OBJEK WISATA WATERBOOM DI KOTA SAWAHLUNTO - Dola Permata Sari; Marwan Usman; Rose Rahmidani (Jurnal Ecogen, 2018)
The purpose of this research is to know the influence of product, price, promotion, place, physical evidence, employee, process, productivity and quality to decision of tourist visiting at Waterboom tourist object. This type of research is causative. The population in this study is all tourists who visit the tourism object that is Waterboom in Sawahlunto city. The number of research samples was determined based on Cochran formula of 100 people and was chosen by using accidental sampling technique. The data that are used are the primary obtained through the distribution of questionnaires to selected tourists. The analytical method used is descriptive and quantitative analysis through path analysis. The results of this study indicate that: (1) The product has a significant influence on the tourist visiting decision on Waterboom tourism object, (2) Price has no significant effect on tourist visiting decision at Waterboom tourist object, (3) Promotion has no significant effect on tourist visiting decision on Waterboom tourism object, (4) Place  has no significant effect on the tourist visiting decision on the Waterboom tourist object, (5) Physical evidence has a significant effect on the decision of tourists visiting the tourist object, that is Waterboom, (6) Employees have no significant effect on tourist visiting decisions on Waterboom tourist object, (7) The process has a significant influence on the decision of tourists visiting the tourist object that is Waterboom, (8) Productivity and quality significantly influence the decision of tourists visiting the Waterboom tourist object.Keywords: Visiting Decision, Product, Price, Promotion, Place, Physical Evidence, Employee, Process, and  Productivity and Quality